Zebrafish Fukutin family proteins link the unfolded protein response with dystroglycanopathies - Lin, Yung-Yao (Oxford University Press, 2011)
Allelic mutations in putative glycosyltransferase genes, fukutin and fukutin-related protein (fkrp), lead to a wide range of muscular dystrophies associated with hypoglycosylation of α-dystroglycan, commonly referred to as dystroglycanopathies. Defective glycosylation affecting dystroglycan–ligand interactions is considered to underlie the disease pathogenesis. We have modelled dystroglycanopathies in zebrafish using a novel loss-of-function dystroglycan allele and by inhibition of Fukutin family protein activities. We show that muscle pathology in embryos lacking Fukutin or FKRP is different from loss of dystroglycan. In addition to hypoglycosylated α-dystroglycan, knockdown of Fukutin or FKRP leads to a notochord defect and a perturbation of laminin expression before muscle degeneration. These are a consequence of endoplasmic reticulum stress and activation of the unfolded protein response (UPR), preceding loss of dystroglycan–ligand interactions. Together, our results suggest that Fukutin family proteins may play important roles in protein secretion and that the UPR may contribute to the phenotypic spectrum of some dystroglycanopathies in humans.